Studi Deskriptif Pembuatan Karya Berbahan Serutan Pensil dengan Teknik Menempel pada Kelas IV SD Negeri 168 Bengkulu Utara - Adeska, Meva; Tarmizi, Pebrian; Parmadie, Bambang (JURIDIKDAS, 2024)
This study aims to describe the process of making work made from pencil shavings with a sticking technique in class IV SD 168 168 North Bengkulu. The types and methods of this research are qualitative research and descriptive methods with participative observation techniques. The subject of the research was the fourth grade students elementary school of 68 North Bengkulu. The research instrument is human instrument. Data collection techniques using observation, interviews and documentation. Data analysis of the process of making work made from pencil shavings with sticking techniques is done by analyzing the data, displaying the data, condensing the data and conclusions. Data analysts of the work are discussed by looking at the elements of fine arts, fine arts principles and a combination of techniques. The process of making work made from pencil shavings by sticking to class IV SD Negeri 168 North Bengkulu, namely preparing tools and materials, making sketches on drawing paper in accordance with the desired shape, attaching pencil shavings to the part that has been smeared and coloring the image. Nine works made by students are seen from the elements of fine arts, fine arts principles and a combination of techniques.